The struggle for power during the reign of Sultan Mahmoud bin Mohammad bins Malikshah Seljuk (511-525 A.H. / 1117-1130 A.D.) - Nayef Alqaedah, Abdelhadi (Opción)
Modern studies have been concerned with the great Seljuk sultans and devoted many works and studies to address its crucial aspects. The current study attempts to shed light on the internal conflicts between members of the Seljuk family in the Sultanate of Mahmoud bin Mohammad, and the major transformations that took place giving that he occupied the Sultanate throne where the sultan who was sitting on the throne of Iraq and Persia was the only sultan in the state. Nevertheless, this matter has changed after the arrival of Sultan Mahmoud bin Mohammed to the Sultanate, and therefore, studying his reign and the internal conditions during it constructs the basis for understanding the development of the Seljuk Sultanate in particular and the system of the Sultanate in general.